Website Omah Tinom Jogja sebagai Media Pengenalan Jenis Usaha dan Pemasaran Online - Indah Susilawati; Imam Suharjo; Putry Wahyu Setyaningsih (Yayasan Kajian Riset dan Pengembangan RADISI, 2021)
Omah Tinom Jogja is a joglo rental business for various community activities. At the end of 2020, Omah Tinom Jogja expanded their business by opening a culinary with the theme of ‘old food and drinks’ and rental homestays in the same location. The problem faced was that the grand opening which was held in December 2020 was constrained by the government's restrictions on people's movement related to the COVID-19 pandemic. This condition has an impact on various community activities, including the sustainability of community businesses at all scales. Government policies make various community activities goes virtual by utilizing information technology, business actors are also present in virtual spaces to introduce types of business and product marketing. By considering the conditions and facts, Omah Tinom Jogja took the solution offered by the PkM FTI UMBY Team to utilize information technology as a medium for introducing business types and online marketing strategies. A website for Omah Tinom Jogja was developed to more quickly introduce the type of business Omah Tinom Jogja to the public.